حال المنازعات الناشئة عن التقصير في عقد الإيجار: دراسة في شركة BOWRIZ لإجارة السيارات بماجيلانج في منظور الشريعة الإسلامية - Lahuri , Setiawan; Putra , Okky Mahdi Indrawan; Zuhroh , Ainun Amalia (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
Along with the development of the times, several people or companies that are engaged in car rental have emerged because of the importance of transportation, especially cars and very expensive car prices. From this rental, a lease agreement or ijarah emerg es. For rental owners and tenants, they want to get mutually beneficial reciprocity, but in reality, on the ground, there is a situation where achievement is not achieved or is said to be "default". The default also occurred in Bowriz's car rental, which w as the object of the research. From this explanation, a problem arose, namely how the practice of resolving default disputes at Bowriz car rental and how to review Islamic law on the settlement. This study aims to determine the practice of settlement of de fault disputes in Bowriz car rental and a review of Islamic law on its settlement. Data collection methods are interviews, direct observation, and asking for some car rental documents. The problems that exist in the study are then analyzed using qualitativ e analysis methods with an inductive approach. The Islamic law used is the principle of Mu'amalah which has been recommended by the Quran and Sunnah. The results of the research conducted indicate that the settlement of the default dispute is resolved by u sing deliberation and mediation. Both methods are in accordance with Islamic law because they prioritize the principle of Mu'amalah. and asked for some car rental documents. The problems that exist in the study are then analyzed using qualitative analysis methods with an inductive approach. The Islamic law used is the principle of Mu'amalah which has been recommended by the Quran and Sunnah. The results of the research conducted indicate that the settlement of the default dispute is resolved by using delibe ration and mediation. Both methods are in accordance with Islamic law because they prioritize the principle of Mu'amalah. and asked for some car rental documents. The problems that exist in the study are then analyzed using qualitative analysis methods wit h an inductive approach. The Islamic law used is the principle of Mu'amalah which has been recommended by the Quran and Sunnah. The results of the research conducted indicate that the settlement of the default dispute is resolved by using deliberation and mediation. Both methods are in accordance with Islamic law because they prioritize the principle of Mu'amalah. The results of the research conducted indicate that the settlement of the default dispute is resolved by using deliberation and mediation. Both m ethods are in accordance with Islamic law because they prioritize the principle of Mu'amalah. The results of the research conducted indicate that the settlement of the default dispute is resolved by using deliberation and mediation. Both methods are in acc ordance with Islamic law because they prioritize the principle of Mu'amalah.